Effects of intermediary reservoir in a two-stage impedance pump - Lee, Vincent; Chong, J. (2017)
© 2017 The Authors, published by EDP Sciences. Impedance pump is a simple valve-less pumping mechanism, which transport fluid through the mismatch of impedance in the system. A typical open-loop impedance pump consists of an elastic tube, connected to rigid tubing, where the rigid section is connected to a reservoir. Mismatch in impedance occurs when an asymmetrical periodic excitation is exerted on the elastic tube. Studies showed that sequential excitations on the elastic tube infers higher volumetric efficiency than a single excitation. This work studies the effects of an intermediary reservoir between two excitation points on an elastic tube. This study aims to shed some light on the steady state response and fluid motion within the intermediary reservoir; in which increased volumetric efficiency is demonstrated.